Construction and validation of an instrument for evaluating Lean Healthcare in healthcare institutions - Hellen Maria de Lima Graf Fernandes; Dirceu da Silva; Rosana Ribeiro Tarifa; Edinêis de Brito Guirardello (Universidade Federal do Rio Grande do Sul, 2024)
ABSTRACT Objective: To build and validate an instrument to evaluate Lean Healthcare in healthcare institutions. Method: Methodological study conducted in three stages: 1) Instrument construction; 2) Content validity using the Delphi technique with 14 experts; and 3) Construct validation using Structural Equation Modeling with sample consisted of 113 professionals with experience in Lean Healthcare. Data collection carried out from October/2020 to January/2021 using a digital form. Data analysis performed with the SmartPLS2.0/M3 software. Results: Items were developed after an integrative review and divided into the dimensions Structure, Process and Outcome, according to Donabedian's theoretical framework. Content validation in two rounds of the Delphi technique. Final instrument, after model adjustment, containing 16 items with Cronbach's alpha of 0.77 in Structure, 0.71 in Process and 0.83 in Outcome. Conclusion: The instrument presented evidence of validity and reliability, enabling its use in healthcare institutions to evaluate Lean Healthcare.